IMPACT OF NUTRITIONAL COUNSELLING ON BODY MASS INDEX (BMI) AND NUTRIENT INTAKE OF THE NON - COMMUNICABLE DISEASE PATIENTS (NCD) - Singh, Manisha; Chakravorty, A; Gupta, K K; Agrawal, N K (Indian Journal of Community Health, 2011)
Good health is an important discussion of the quality of life. Health problem is a major concern in all over the world but especially in developing countries. Non-communicable diseases ( NCDs) contribute the ill health. Diabetes, coronary heart disease, various forms of cancer, gastro intestinal disorder and various diseases of bones and joints are diet related NCDs. Nutritional counselling is one of the effective tools of changing the food habits of people. The data for this study is taken from the out patients services of Department of Endocrinology & Metabolism and Cardiology of Sir Sunder Lal Hospital, Banaras Hindu University, Varanasi-5. Total 250 samples were included in the study. Age group 40 – 60 years were considered as study samples who attended the Endocrinology and Cardiology departments. Purposive sampling method was used in the study. Questionnaire cum interview method was adopted in the study. Anthropametric measurements were taken by using standard techniques. 24 hours diet recall method was also used in this study. Evaluation of councelling was done on basis of changes in BMI and nutrient intake. Result shows the positive impact of nutritional counselling in BMI and nutrient intake of NCD patients.